(untitled) (Latakia University Journal -Biological Sciences Series, 2018)
تم في هذا البحث دراسة تأثير إضافة الحمض الأميني "اللايسين" إلى الخلطة العلفية في نمو أسماك الكارب العادي Cyprinus carpio L. المرباة في 8 أحواض زجاجية سعة كل منها 40 ليتراً، وضع في كل حوض 8 إصبعيات من سمك الكارب العادي بمتوسط طول قياسي 7.5سم ± 0.05 ومتوسط وزن 12.25غ ± 0.57، تم إضافة اللايسين بنسب مختلفة (شاهد دون إضافة اللايسين, 2%, 3% و4%) إلى الخلطة العلفية. زُودت الأحواض بفلاتر ومضخات أوكسجين، عُلفت الأسماك مرتين يومياً وحتى الشبع. بينت نتائج الدراسة وبحساب معدل النمو المطلق ومعدل النمو النوعي ومعامل التحويل الغذائي، أن المعاملة (L1) التي أضيف إليها اللايسين بنسبة (2%) من الوزن الكلي للخلطة قد تفوقت معنوياً على المعاملات الثلاث الأخرى إذ بلغ معامل التحويل الغذائي (2.2)، وكان معدل النمو النوعي (0.28 %/يومياً). This research aimed to study the effect of adding different rates of lysine on the weight and growth of common carp fingerlings. The experiment was carried out in the laboratory for 4 months using eight glass containers (40 liters each) with four treatments (L0 no Lysine addition, L1 (2%), L2 (3%), L3(4%) of the total weight of diet. Eight common carp fingerlings (average of tall 7.5cm ± 0.05 and average of weight 12.25g ± 0.57) were cultured in each container with Oxygen pumps and filters. Results showed by growth rate, absolute growth rate, specific growth rate and food conversion ratio (FCR) that the treatment L1 (2% lysine) was significantly the best comparing to the other treatments, where FCR was (2.2) and the specific growth ratio was (0.28 %)